A study of consumer preferences for customized product design - Wedowati Endang Retno; Singgih Moses Laksono; Gunarta I Ketut (MATEC Web of Conferences, 2018)
Segmentation has been frequently used to study individual consumer behavior against its preference. Consumer preferences indicate consumer requirements for a product. This study aims to analyze consumer preferences based on gender segmentation (male and female) and age segmentation (adolescents, adults, and elderl y). Consumer preferences wer e studied based on three aspects, namely functionality, usability, and pleasure that are applied to food products. Respondents consisted of 225 consumers of ice cream products. Crosstab analysis was used to describe consumer preferences, while chi-square test was applied to analyse the difference of consumer preference based on predetermined segmentation. The result showed that there was no significant difference for male and female consumer preferences for three aspects. Furthermore, on the attributes of taste (functionality), shape (usability) and appearance (pleasure) there were significant differences. Based on the age segmentation there were differences in consumer preferences for aspects of functionality and pleasure. Howe ver, we also found that there was no significant difference in product attributes of those aspects, except for the colour attribute. Different consumer preferences obtained in different segments can be used as a reference to customer requirements for design ing customized products. Ultimately, the products can be tailored to consumer preferences in each segment.